PENGARUH PEMBERIAN PUPUK PETROGANIK DAN KOMPOS PADA VERTISOL BEKAS GALIAN PEMBUATAN BATU BATA TERHADAP SERAPAN N SERTA PERTUMBUHAN TANAMAN JAGUNG - Bambang Siswanto; Widowati Widowati (Universitas Tribhuwana Tunggadewi, 2017)
The low level of farms income from agricultural sector mainly happens in dry season had to inappropriate soil cultivation. The utilization of soil for brick ste manufacturing is one of this case. The excavation process occurs on top soil inflicting degradation of soil fertility. Soil in the impact of this condition has a problem in providing chemical element for the agriculture, especially the lack of N. One of alternative attempts to increase the soil fertility in providing N on formerly brick ste excavation-soil is by supplying Petroganik fertilizer and compost. Petroganik and compost is an organic fertilizer containing N, P, K, the other nutrient, similar to the other organic fertilizers. The aims of the research are to determine the effect Petroganik fertilizer and compost application on N uptake and toward the growth of corn on former brick ste excavation-soil, and to know the chosen dosage which is resulting in growth and N uptake of corn. Research used is Random Block Design with 9 treatment and 3 replication. Dosage of treatment T0 : Control, Petroganik (14, 17, 20, 23) t/ha and compost (14, 17, 20, 23) t/ha. Indicator plant was used Hybrid Corn BISI 2. The result of experiment showed that : 1. Significant effect in increasing uptake of N the corn. The treatment of Petroganik 17 t/ha (P2) increasing 145 % and compost 14 t/ha (P2) increasing 93.8 %, 2. Insignificant effect on plant growth (height, number of leaf) However, it gives significant effect on dry weight of the corn biomass. The treatment Petroganik 17 t/ha (P2), increases 101.45 %, 3. The application of Petroganik fertilizer is more effective in increasing the growth and N uptake of corn than that of compost since the application of 17 t/ha of Petroganik has already increased the N uptake and growth of corn .